POLITICAL PARTY AS AN ESSENTIAL ACTOR OF THE PUBLIC SECTOR - FINANCIAL BUSINESS OF PARTIES - Abdalah, Hajet (Political Review, 2023)
The business of political parties in all countries of the world in the modern era should be legally regulated. However, the financial side of the business of all parties is something that has always attracted attention. Accordingly, cash flows are constantly being checked, as well as the resulting deficit. However, it must be confirmed that there are also a number of parties that clearly state how and where all the money spent goes. Taxes and membership fees are some of the items that represent money that comes into the hands of political parties. All this, from the legal point of view, represents one of the bases for regulating their business from the economic point of view.
Keywords: party; politics; economics; money; business